Maxillary molar enamel thickness of Plio-Pleistocene hominins. Issue 142 (May 2020) - Lockey, Annabelle L.; Alemseged, Zeresenay; Hublin, Jean-Jacques; Skinner, Matthew M.
Abstract: Enamel thickness remains an important morphological character in hominin systematics and is regularly incorporated into dietary reconstructions in hominin species. We expand upon a previous study of enamel thickness in mandibular molars by examining a large maxillary molar sample of Plio-Pleistocene hominins (n = 62) and a comparative sample of extant nonhuman apes (n = 48) and modern humans (n = 29). 2D mesial planes of section were generated through microtomography, and standard dental tissue variables were measured to calculate average enamel thickness (AET) and relative enamel thickness (RET). AET was also examined across the lingual, occlusal, and buccal regions of the crown. This study confirms previous findings of increasing enamel thickness throughout the Plio-Pleistocene, being thinnest in Australopithecus anamensis and peaking in Australopithecus boisei, with early Homo specimens, exhibiting intermediate enamel thickness. Agreeing with previous findings, 2D plane of section enamel thickness is found to be a poor taxonomic discriminator, with no statistically significant differences observed between fossil hominins. For fossil hominins, modern humans, and Pongo, the occlusal region of enamel was the thickest, and the lingual enamel thickness was greater than buccal. Pan and Gorilla present the opposite pattern with enamel being thinnest occlusally. Comparison at each molar position between the maxilla and mandible revealed very few significant differences in fossil hominins but some evidence of significantly thicker maxillary enamel (AET) in modern humans and thinner maxillary enamel in Pan (RET).